2003
DOI: 10.1152/ajpendo.00024.2003
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of glucose production by GLP-1 independent of islet hormones: a novel extrapancreatic effect

Abstract: . Suppression of glucose production by GLP-1 independent of islet hormones: a novel extrapancreatic effect. Am J Physiol Endocrinol Metab 285: E701-E707, 2003. First published May 28, 2003 10.1152/ ajpendo.00024.2003.-Glucagon-like peptide-1 (GLP-1) is an intestinal hormone that stimulates insulin secretion and decreases glucagon release. It has been hypothesized that GLP-1 also reduces glycemia independent of its effect on islet hormones. Based on preliminary evidence that GLP-1 has independent actions on en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
130
2
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(145 citation statements)
references
References 56 publications
10
130
2
3
Order By: Relevance
“…In type 2 diabetes, liraglutide, a long-acting GLP-1 derivative, decreased fasting EGP as a result of reduced glycogenolysis [40], and increasing GLP-1 concentrations by dipeptidyl peptidase-4 inhibition with vildagliptin increased hepatic glucose disposal [41]. In healthy people, the infusion of GLP-1 decreased fasting EGP and tended to increase plasma glucose clearance independent of changes in insulin and glucagon concentrations [42].…”
Section: Discussionmentioning
confidence: 99%
“…In type 2 diabetes, liraglutide, a long-acting GLP-1 derivative, decreased fasting EGP as a result of reduced glycogenolysis [40], and increasing GLP-1 concentrations by dipeptidyl peptidase-4 inhibition with vildagliptin increased hepatic glucose disposal [41]. In healthy people, the infusion of GLP-1 decreased fasting EGP and tended to increase plasma glucose clearance independent of changes in insulin and glucagon concentrations [42].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the lack of association between ΔGLP-1 and M/I in the other groups remains elusive. GLP-1 might suppress hepatic glucose production directly [8] or indirectly by regulating glucagon secretion, which controls hepatic glucose production. The euglycaemic-hyperinsulinaemic clamp, used in the present study without infusion of radioactive-marked-glucose, cannot distinguish between hepatic vs skeletal muscle insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Although originally described as a potent stimulator of glucose-dependent insulin secretion, recent studies [1,2,3,4,5,6,7,8,10,11,12,13] have shown that the intestinal hormone GLP-1 also prevents the onset of diabetes and ameliorates existing diabetes through a mechanism that includes enhancement of beta-cell mass [16,17,18,19,20]. Despite limited evidence that GLP-1 can activate PKB [34], and that PKBα overexpression enhances beta-cell mass in vivo [27,28], no studies have shown whether PKB is essential for GLP-1-induced beta-cell proliferation and/or prevention of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It possesses a variety of anti-diabetic actions that are mediated at the level of the beta cell, as well as in peripheral tissues. These include not only the stimulation of glucose-dependent insulin secretion [3,4,5], but also the inhibition of glucagon release [6,7], gastric emptying [7,8] and food intake [9,10], and possibly also enhancement of insulin sensitivity [11,12]. Consistent with these biological actions, long-term treatment of Type 2 diabetic patients with GLP-1 decreases HbA 1c values and is associated with lower fasting and postprandial glucose concentrations and reduced body weight [13].…”
mentioning
confidence: 99%